(untitled) (Ibrahim Cardiac Medical Journal, 2025)
Background & objective: Diabetes mellitus is a growing global health concern characterized by chronic hyperglycemia and associated complications, including hepatotoxicity. Traditional herbal remedies like Foeniculum vulgare (fennel) have recently garnered attention for their potential therapeutic benefits. This study investigates the hepatoprotective roles of fennel in alloxan-induced male diabetic rats. Methods: An experimental study was conducted at Sir Salimullah Medical College, utilizing 30 Wistar albino male rats (90-120 days old). Following a 14-day acclimatization, the rats were divided into three groups: normal control, alloxan-induced diabetic control, and an experimental group treated with fennel extract (150 mg/kg/day) for 21 days post-alloxan induction. Blood samples were collected for glucose and insulin measurement, and liver function tests (Total Bilirubin, ALT, AST) were performed. Histopathological examinations of liver tissues were also conducted. Results: Initial fasting blood glucose levels were comparable across groups; however, by Day 22, the alloxan-induced diabetic control group showed significantly higher levels compared to the fennel-treated group (p < 0.001). At the end of the study on Day 22, significant differences were observed in serum levels of total bilirubin, ALT, and AST among the three experimental groups (p < 0.001). The alloxan-induced diabetic group (Group A2) showed the highest levels of these liver function parameters, while the normal control group (Group A1) had the lowest. Post-hoc analysis indicated that Group A2 had significantly elevated levels compared to both the fennel-treated group (Group B) and Group A1 (p < 0.001 for all comparisons). Histopathological examination revealed that all rats in Group A1 exhibited normal liver histology, whereas all rats in Group A2 displayed abnormal findings. In Group B, 80% of the rats showed normal liver histology, while 20% had mild changes. These results highlight significant differences in liver histopathological outcomes across the three groups (p < 0.001). Conclusion: The findings suggest that Foeniculum vulgare effectively protects against alloxan-induced hepatotoxicity in male diabetic rats, evidenced by improved biochemical parameters and histological integrity of liver tissues. This study underscores the potential of fennel as a therapeutic option for managing diabetes and its associated hepatic complications. Ibrahim Card Med J 2024; 14(1): 46-53